ANALISIS ALUR KERJA SPO2 PADA ALAT PATIENT MONITOR - Abdul Haris Al Baihaki; Khairil Abdillah (JURNAL MUTIARA ELEKTROMEDIK, 2018)
Oxygen saturation(Sp) is one of the parameters in the patient's device The monitor is used as a measurement of oxygen levels in the blood Non-invasive measurements whose results are directly displayed on LCD. Measurement of oxygen levels in the blood using this device is equivalent by using measurement using pulse oxymetry. Aim research to find out the Sp workflow on patient monitoring devices, research held on July- August, 2018 at Sari Hospital Mutiara medan, the study was carried out on the device Patient Monitor brand L-Gemedical system, type-CF generated Sp waveform is the Sp value and the limit larm, the input of this system is the LED sensor and Photodioda which produces the light transmission process on the finger and the results of the measurement tool will be displayed on the display screen in the form of a number value.